2005
DOI: 10.1021/jf0508753
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Absorption and Hydrolysis of Ethyl α-d-Glucoside in Rat Intestine

Abstract: Ethyl alpha-D-glucoside (alpha-EG) is normally contained in Sake, which has been taken by Japanese people since ancient times. In this study, the intestinal absorption of alpha-EG was investigated using rat everted intestinal sac. Furthermore, the alpha-EG hydrolytic activity in rat intestine was compared with disaccharides hydrolytic activities, and the effects of alpha-EG on disaccharides hydrolysis were examined using crude enzyme preparation from rat intestinal acetone powder. Glucose liberated from alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Maltose and commercial IMOs were used as controls. The indigestible products were determined by HPAEC-PAD [23,24].…”
Section: Digestion Testmentioning
confidence: 99%
“…Maltose and commercial IMOs were used as controls. The indigestible products were determined by HPAEC-PAD [23,24].…”
Section: Digestion Testmentioning
confidence: 99%
“…7) Furthermore, -EG was detected in the plasma of rats fed -EG solution as a daily drink. 8) As shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…8) Some -EG was hydrolyzed in the small intestinal mucosa before absorption, and subsequently -EG absorbed into blood stream was presumably metabolized in the kidneys, but in an in vitro examination, hydrolyzing activity for -EG was much lower than that for disaccharides. 7,8) Hence ingested -EG was not hydrolyzed completely, and consequently it was excreted into the urine. On the other hand, the -EG administered was recovered from the urine as well as -EG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] Experiments have shown that, in mice, α-EG is absorbed by intestinal epithelial cells via sodium-dependent glucose transporter 1. 11) A study in human volunteers had demonstrated that approximately 80% of α-EG was promptly discharged through urine within 24 h after ingestion. 12) Based on these reports, we postulated that α-EG was likely transported to the stratum corneum after being absorbed by the small intestine and transferred into circulation.…”
mentioning
confidence: 99%